Novel Romance Sebagai Pembelajaran - Putra Rian Hermawan (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The novel has several genres based on the storyline, one of which is the romance genre novel which is more in demand, this is inseparable from the storyline which is more relevant or in accordance with the love stories of the readers, as well as the storyline which is interesting and not boring to read. read, the last reason is that there are also many words or quotes that can be quoted related to life. But apart from that reading novels must also have a positive impact on readers, not just reading for pleasure. By inserting good things such as friendship or moral values ​​that must be contained in the novel will make the reader get good things after reading the novel, avoid things that make the reader do something out of line because he has read the novel.